PENGARUH CSR, GENDER TERHADAP NILAI PERUSAHAAN LQ-45 - Anisa Angel Lina; Ella Ramadhanti; Aneza Zubaida (Universitas Muhammadiyah Bengkulu, 2025)
of the things that investors pay the most attention to when they invest is the value of the company because it shows how resilient the company is in the future. The company's long-term goal is to increase profits. To maximize the achievement of a company's value, it is important to consider the company's value, including all the factors that influence it. The purpose of this study is to determine the influence of Corporate Social Responsibility and Gender Diversity on LQ45 Company Value in 2018–2023. This method uses applying purposive sampling to collect data samples. There are 9 companies from the LQ45 sector as a sample in this study. The data will be analyzed by quantitative research methods in the form of secondary data using IBM SPSS 26 and the Classical Assumption test, namely the normality test, multicollinearity test, heterokedasticity test, autocorrelation test. T he results of the study are (1) CSR has a negative effect on company value, (2) gender on company value has a positive effect on company value. Keywords: CSR, Gender, Nilai Perusahaan LQ-45